Re-evaluation of the Cerebral Palsy’s orthotic need in Adaptive Seating Orthosis (ASO) design - Muhammad Jameel, Mohamed Kamil; Mohd Najib, Abdullah Sani (University of Novi Sad, 2023)
Adaptive seating orthosis (ASO) for Cerebral Palsy (CP) patients in Malaysia mostly are imported, highly expensive for the bottom millions, bulky and complicated design structure, and not accommodating users’ preferences. Through a study involving 10 CP patients with their parents/guardians in Malaysia, the goal of this paper is to re-assess the design needs of CP’s orthotic in ASO design. The purpose of the study is to identify the difficulties, as well as the ergonomic and functional problems, in caring for CP patients with the current ASO. The result of the study revealed several of the problems that parents/guardians face while taking care of the CP patient, mainly caused by technical flaws in the current ASO design. Therefore, a few design criteria have been proposed to solve the addressed problems. The contribution of this study will help as a preference for the improvement and development of ASO design.